Upaya Menurunkan Nyeri Melalui Senam Ergonomis dan Pemberian Rebusan Daun Sirsak Pasien Gout Arthritis di Desa Sekaran - Lafina Widiastuti; Novi Indah Aderita (Indonesian Journal on Medical Science, 2022)
The health office in 2019 stated that there were 1400 gout sufferers from 10 public health center in Klaten, Wonosari public health center as many as 100 cases. These data show that gout in Klaten regency, especially Wonosari district is still quite high (Klaten health office, 2019). Gout causes problems, one of which is pain. The purpose of this study was to describe the management of ergonomic exercise and administration of soursop leaf decoction with acute pain nursing problems. Methods of data collection by observation, measurement, and documentation. The instrument uses a medical surgical nursing care format, observation sheets, GCU tools. The results of the study obtained assessment data: the subject experienced pain on a scale of six, pain due to increased uric acid levels, pain in the knees, ankles, and calves, pain like stabbing, intermittent pain. Objective data: composmentis awareness, TTV: BP: 130/90 mmHg, RR: 20 x/minute, N: 82 x/minute, S: 36.7 C, face: the patient's expression seems to be holding back pain. Nursing actions include assessing the characteristics of pain, doing ergonomic exercises and giving soursop leaf decoction. After nursing care was carried out seven times for one week, the results of pain decreased from a scale of six to a scale of 3, the results of the examination of uric acid decreased with a decrease in the range of 2.2-4.3 mg/dl. The acute pain problem is resolved and the action is effective in reducing pain.